2016
DOI: 10.3389/fphar.2016.00447
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-Induced cPLA2 Expression via NADPH Oxidase/Reactive Oxygen Species-Dependent NF-κB Cascade on Human Pulmonary Alveolar Epithelial Cells

Abstract: Tumor necrosis factor-α (TNF-α) triggers activation of cytosolic phospholipase A2 (cPLA2) and then enhancing the synthesis of prostaglandin (PG) in inflammatory diseases. However, the detailed mechanisms of TNF-α induced cPLA2 expression were not fully defined in human pulmonary alveolar epithelial cells (HPAEpiCs). We found that TNF-α-stimulated increases in cPLA2 mRNA (5.2 folds) and protein (3.9 folds) expression, promoter activity (4.3 folds), and PGE2 secretion (4.7 folds) in HPAEpiCs, determined by Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 57 publications
(91 reference statements)
3
22
0
Order By: Relevance
“…It was found that the activation of NADPH oxidase in alveolar epithelial cells is a source of ROS production [42]. Inhibition of NADPH oxidase by apocynin or diphenyleneiodonium chloride reversed TNF-α-mediated cPLA2α expression [43]. Here, we found that the stimulation of leptin promoted p47 phox phosphorylation and ROS production in an OB-R-dependent manner.…”
Section: Discussionsupporting
confidence: 57%
“…It was found that the activation of NADPH oxidase in alveolar epithelial cells is a source of ROS production [42]. Inhibition of NADPH oxidase by apocynin or diphenyleneiodonium chloride reversed TNF-α-mediated cPLA2α expression [43]. Here, we found that the stimulation of leptin promoted p47 phox phosphorylation and ROS production in an OB-R-dependent manner.…”
Section: Discussionsupporting
confidence: 57%
“…NADPH oxidase (NOX) activity was measured using lucigenin as described elsewhere [ 13 ]. Briefly, the coculture cells or the activated HSCs were harvested after culturing for 24, 48, or 76 hours and centrifuged at 400 ×g for 10 min at 4°C, and the cell pellet was kept on ice after resuspended by 35 μ l/per well of the ice-cold RPMI-1640 medium.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the important role that PGES-1 plays in producing high levels of PGE-2, developing novel drug inhibitors of this enzyme is now an important pharmaceutical research focus [92,93]. Finally, both the expression of the phospholipase A2 gene as well as the activity of the enzyme can be increased dramatically by UVB [94,95], by NADH oxidase pathways [96], by MAPK and NF-kB pathways activated by IL-beta, TNF-alpha, and EGF receptors [97], and by cAMP signaling pathways [94,95,98,99].…”
Section: Regulation Of Pge-2 Production In Skinmentioning
confidence: 99%
“…Exposure of keratinocytes, fibroblasts or immune cells to such stimuli as UVB radiation, IL-1, ROS, or Lipopolysaccharide (LPS) can result in increased COX-2 gene expression, as well as increased activity of the genes for PGES and PLA2 [83,95]. By blocking the signaling pathway that leads to activation of transcription factors, particularly NF-kB that regulates these genes, natural anti-inflammatory compounds can block not only COX-2 expression, but expression of PGES [83] and/or cPLA2 [96,189]. A few examples of some natural compounds that block PGE-2 production, as well as other inflammatory mediators, are discussed below:…”
Section: 83mentioning
confidence: 99%